Shorinji kempo basic technique training method based on local wisdom for beginners kenshi - Carles Nyoman Wali; Widiyanto (Journal Sport Area, 2021)
The lack of training models and training creativity in creating traditional game-based training models for kenshi to improve the basic techniques of kempo becomes problems in this study. The purpose of this research is to produce a model of basic martial arts techniques of kempo through traditional games for kenshi beginners. This research is a research and development (R&D) research which was adapted into 8 steps in research: 1). Field news collection 2). Breakdown of the news that has been collected 3). Elaborating initial creation 4). Expert validation and revision 5). Small scale trial 6). Large-scale trial 7). Making the final product 8). Product effectiveness test. The small-scale trial subjects of 20 beginners kenshi were taken from 2 dojos, namely the Panjatan Junior High School dojo and the Amikom dojo. The large-scale test subjects totaling 45 beginners kenshi were taken from 3 dojos, namely Balong, Triharjo, and SD Gunung Kidul. The subjects in this study came from 5 dojos in Perkemi DIY. Data were collected through interviews, distributing questionnaires, field notes, evaluation, and assessment rubrics for beginner kenshi. The results of this study are in the form of training models for basic techniques of kempo martial arts through traditional games for beginner kenshi, and there are five training models: 1. gobak sodor, 2. yeye, 3. pahtil catfish, 4. zogdag, 5. stick dance. Based on the results of this study, it can be concluded that the traditional game-based kempo martial arts training model for kenshi beginners is feasible to use. The author's recommendation to other prospective researchers is to examine traditional games in an approach with other disciplines and use professional research subjects in other sports.